SYMBOLISM IN EDWARD ALBEE'S THE ZOO STORY - Utami, Aprilia Nur Cahya (2009)
The objectives of the study are to analyze the structural element of Edward Albee's The Zoo Story and to analyze the meaning of the symbols employed in this play. In collecting the data the writer uses library research or document analysis.The data are taken from the dialogue of the play.This research employs the theory of Symbolism by Perrine and supported by some other theorists. The result of the study shows that first; in the dialogue of the play, Edward Albee tries to symbolize the social condition that occurs at that time. Second; Edward Albee uses the structural elements of the play to give responses, opinion, and sympathy to the social gap that occurs.